Penguatan Karakter Peserta Didik Dalam Program PLP Melalui Pembelajaran Al-Islam di SMK Muhammadiyah I Surabaya - Murwanti, Murwanti (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2026)
Abstract: Strengthening students' character is one of the main goals in the world of education. This study aims to analyze students character stregthening through Al-Islam learning in the School Field Introduction (PLP) program at SMK Muhammadiyah I Surabaya. The research employs a qualitative approach using observation, interviews, and documentation as data collection techiques.The methods used include learning assistance, instilling Islamic character values ??through Al-Islam material, and habituating religious attitudes in teaching and learning activities. The results of the activity show that Al-Islam learning in the PLP program is able to provide a positive contribution to strengthening students' character, especially in aspects of religiosity, discipline, responsibility, and social attitudes. This activity is expected to be one of the sustainable efforts in supporting character education in schools.